Synthesis Characterization and DFT Studies of New Azo Dye Derived from Dapsone and Evaluation it as Corrosion Inhibiter - Ashraqt Ahmed, Adnan Sultan (Forest Chemicals Review, 2022)
The azo dye (A3) has been synthesized and characterized by FT-IR, 1H NMR and 13C NMR spectroscopic techniques. The compound (A3) has been evaluated as carbon steel corrosion inhibitor at different concentrations (0.0001, 0.0005, 0.001and 0.005 mM) and different temperatures (298-318 K). The corrosion inhibition efficiency was studied by Potentiodynamic polarization. The effects of concentration and temperature on the inhibition efficiency were studied by Potentiodynamic polarization measurements, the results showed that increasing concentration of (A3) increases the inhibition efficiency while increasing the temperature decreases it, the highest corrosion inhibition efficiency, 92.2 % was recorded with 0.005 mM of A3at 298 K in 1 M HCl. The adsorption process was found to obey Langmuir isotherm, and the adsorption thermodynamic parameters were studied.Computational chemistry calculations were accomplished using density functional (DFT) method. Theoretical and experimental methods were discussed and the findings displayed that the inhibition efficiency values by closely agreed